The Relationship Between Contact Characteristics with TB symptoms Presence in Patient’s Contact of Pumonary TB BTA+ - Reny Mareta Sari (Universitas Airlangga, 2014)
Patients with Tuberculosis (TB) can infect 10-15 people for 1 year, especially in those who are often in direct contact with sufferers. The number of TB patients with positive acid-resistant bacteria (BTA+) patients in the Public health center (PHC) of Tanah Kali Kedinding continued to increase from 2011 to 2013. This study aims to analyze the relationship between contact characteristics with the presence of symptoms in contact with pulmonary TB patients with BTA+. This study uses a cross-sectional design. The research sample was the contact of TB patients with BTA+ who were in the working area of the Tanah Kali Kedinding Health Center in Surabaya in 2013. The dependent variable was the contact status marked by the presence of TB symptoms in contacts experienced after the patient was diagnosed with smear pulmonary TB patients with BTA+. Statistical test results with α = 0.05 indicate that age (p = 0.010), contact-patient relationship status (p = 0.028), and place of residence (p = 0.027) have a relationship with symptoms on contact with pulmonary TB patients with BTA+. While gender variables (p = 0.273), an education level (p = 0.201), and work status (p = 0.328) have no relationship with symptoms on contact, so it can be concluded that age, contact-patient relationship status, and residence have a relationship with the symptoms of contact, while gender, education level, and work status do not have a relationship with the symptoms of TB in contact with pulmonary TB patients with BTA+.